2016
DOI: 10.1021/acschemneuro.5b00274
|View full text |Cite
|
Sign up to set email alerts
|

Perindopril Attenuates Lipopolysaccharide-Induced Amyloidogenesis and Memory Impairment by Suppression of Oxidative Stress and RAGE Activation

Abstract: Clinical and preclinical studies account hypertension as a risk factor for dementia. We reported earlier that angiotensin-converting enzyme (ACE) inhibition attenuated the increased vulnerability to neurodegeneration in hypertension and prevented lipopolysaccharide (LPS)-induced memory impairment in normotensive wistar rats (NWRs) and spontaneously hypertensive rats (SHRs). Recently, a receptor for advanced glycation end products (RAGE) has been reported to induce amyloid beta (Aβ1-42) deposition and memory im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 50 publications
0
12
1
Order By: Relevance
“…Benfotiamine was shown to reduce AGEs formation (Nagai,Shirakawa et al 2014) and reduce diabetic vascular complications (Bozic, Savic et al 2015). ACE inhibition by perindopril was shown to reduce accumulation of AGEs, increase sRAGE (Forbes, Thorpe et al 2005) and reduce oxidative stress and RAGE activation in rats (Goel, Bhat et al 2016). Although perindopril was previously shown to increase sRAGE (Forbes, Thorpe et al 2005) in diabetic patients, however, in the current study similar action was not shown which might be attributed to the difference in disease model, species and dose administered.…”
Section: Discussioncontrasting
confidence: 62%
“…Benfotiamine was shown to reduce AGEs formation (Nagai,Shirakawa et al 2014) and reduce diabetic vascular complications (Bozic, Savic et al 2015). ACE inhibition by perindopril was shown to reduce accumulation of AGEs, increase sRAGE (Forbes, Thorpe et al 2005) and reduce oxidative stress and RAGE activation in rats (Goel, Bhat et al 2016). Although perindopril was previously shown to increase sRAGE (Forbes, Thorpe et al 2005) in diabetic patients, however, in the current study similar action was not shown which might be attributed to the difference in disease model, species and dose administered.…”
Section: Discussioncontrasting
confidence: 62%
“…This may also explains, at least partly, the hepatic oxidative stress and histological changes observed in IR‐subjected rats. PER was previously reported to possess protective effects against oxidative damage in a number of experimental models (Yang et al, ; Goel et al, ). In agreement, data of the present study provide clearly a direct evidence for the antioxidant activity of PER.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of ACE inhibitors could be explained partly via suppressing brain derived neurotrophic factor decline and TNF-α release. They were also found to ameliorate oxidonitrosative stress and nitrotyrosine production ( Ali et al, 2016 ) with that in turn reduces amyloidogenesis and subsequent Aβ deposition ( Goel et al, 2016 ). However, further investigations are required to see if the contradicting reports were intrinsic to the specific inherent nature of the drug or methodological issue.…”
Section: Renin Angiotensin System and Alzheimer’s Disease: Animal Stumentioning
confidence: 99%